2002
DOI: 10.1104/pp.010663
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of a 9-cis-Epoxycarotenoid Dioxygenase Gene in Nicotiana plumbaginifolia Increases Abscisic Acid and Phaseic Acid Levels and Enhances Drought Tolerance

Abstract: The plant hormone abscisic acid (ABA) plays important roles in seed maturation and dormancy and in adaptation to a variety of environmental stresses. An effort to engineer plants with elevated ABA levels and subsequent stress tolerance is focused on the genetic manipulation of the cleavage reaction. It has been shown in bean (Phaseolus vulgaris) that the gene encoding the cleavage enzyme (PvNCED1) is up-regulated by water stress, preceding accumulation of ABA. Transgenic wild tobacco (Nicotiana plumbaginifolia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
176
1
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 385 publications
(190 citation statements)
references
References 25 publications
10
176
1
3
Order By: Relevance
“…The concentration fluctuation of endogenous ABA is considered a signal for the gene expression of proteins such as dehydrins, which is sensitive to cold, drought, and salinity stress [62]. It has also been stated that overexpressing the key regulatory gene involved in ABA biosynthesis can increase ABA concentration in plants and the higher ABA level boosts stress tolerance [63]. Similarly, it has been shown that ABA improves resistance to temperature and salinity stresses by controlling the uptake of water and ions in higher plants [64].…”
Section: Abscisic Acidmentioning
confidence: 99%
“…The concentration fluctuation of endogenous ABA is considered a signal for the gene expression of proteins such as dehydrins, which is sensitive to cold, drought, and salinity stress [62]. It has also been stated that overexpressing the key regulatory gene involved in ABA biosynthesis can increase ABA concentration in plants and the higher ABA level boosts stress tolerance [63]. Similarly, it has been shown that ABA improves resistance to temperature and salinity stresses by controlling the uptake of water and ions in higher plants [64].…”
Section: Abscisic Acidmentioning
confidence: 99%
“…the promoter activity was enhanced by water stress. thompson et al (22) indicated that in leaves of tomato 9-cis-epoxycarotenoids is present in abundance, and the enzyme activities involved in the reaction from xanthoxin to ABA are constitutive (14). therefore, these results provide evidence that leaves and roots may be responsive to water stress resulting in increased ABA accumulation.…”
Section: Expression Of Ahnced1 Mrna and Ahnced1 Protein In Different mentioning
confidence: 86%
“…Thus, induction of AtNCED6 during A. thaliana (Col-0) imbibition increases the ABA level more than 20-fold and this is sufficient to prevent germination; whereas induction of AtNCED6 during seed development increased seed dormancy and reduced or eliminated viviparism. Inducing expression of a bean NCED gene in tobacco (N. tabacum) seeds also using the dexamethasone-inducible system resulted in incomplete suppression of germination (Qin and Zeevaart 2002). On the other hand, the overexpression of AtNCED6 in non-dormant mutants of Arabidopsis tt3 and tt4 (tt refers to a transparent testa; Debeaujon andothers 2000, 2003 ) restores the dormant status (Martínez-Andújar and others 2011).…”
Section: Aba and Loss Of Seed Dormancy: Overview Of The Role Of Nced mentioning
confidence: 96%
“…2). The 9-cis-xanthoxin formation is now considered to be the rate-limiting step and the NCED genes play a pivotal role in ABA biosynthesis (Qin and Zeevaart 2002;Toh and others 2008;Nambara and others 2010). Specifically, the cleavage of xanthophylls (C40) by NCED that generates cis-xanthoxin is a highly regulated point in higher plants (North and others 2007;Jia and others 2011) and although both 9-cis-neoxanthin and 9-cisviolaxanthin are substrates of NCED in vivo, 9-cis-neoxanthin seems to be the major substrate.…”
Section: Involvement Of Nced In Aba Synthesismentioning
confidence: 98%
See 1 more Smart Citation